Is laparoscopic liver resection for hepatocellular carcinoma in patients with well-preserved liver cirrhosis superior to conventional open liver resection? - Beppu, Toru; Hayashi, Hiromitsu; Miyata, Tastunori; Sato, Nobutaka; Yoshida, Yasushi (Laparoscopic Surgery, 2018)
Laparoscopic liver resection (LLR) has become the standard treatment for various tumors of the liver including hepatocellular carcinoma (HCC) (1-3). LLR for liver tumors are considered to possess several perioperative advantages compared with conventional open liver resection (OLR). The Oslo-CoMet is the only randomized-controlled trial (RCT) to provide solid evidence that LLR is safer, less invasive, and cost-effective compared with OLR in patients with colorectal liver metastases (4).